The mentoring of officers commanding in the SA Military Health Service (SAMHS): a military social work perspective - Radebe, Chrystal (Stellenbosch : University of Stellenbosch, 2009)
Thesis (M Social Work (Social Work))--University of Stellenbosch, 2009.